Evaluation of gas separator effect on operability of gas-motor piston compressor valves - Seyidahmadov, Natig (Eastern-European Journal of Enterprise Technologies, 2019)
To increase the efficiency of gas-lift oil and gas production, it is necessary to improve the operation of compressor stations, namely, to increase the reliability of the gas-motor piston compressor units installed in them. It is found that one of the vulnerable units affecting the reliability and efficiency of the gas-motor piston compressor are direct-flow self-acting valves. In the process of preparing gas for transportation, as well as to ensure the reliability and efficiency of the entire production process, it is necessary to eliminate all gas leaks, prevent liquid hydrocarbon components and solids from entering the valve plates. To solve this problem, associated petroleum gas must be cleaned from solids, heavy hydrocarbon components and moisture. To this end, it is recommended to install an additional new design horizontal gas separator on the suction line of gas-motor piston compressors. The usefulness and importance of the new gas separator lie in a more efficient cleaning of associated petroleum gas supplied to the suction of the 1st stage compressor cylinders, which improves compressor performance, minimizing the leakage of valve plates. The new design separator is used to clean gas from coarse and fine-grained dropping liquid, partially liquid in the vapor-phase state and solids. The new separator can also be used in various sectors of the oil and gas industry. The purpose of installing a new gas separator is to increase the efficiency of gas cleaning from liquid and solid impurities